GROWTH RATE DISPERSION (GRD) OF THE (010) FACE OF BORAX CRYSTALS IN FLOWING SOLUTION - Suharso Suharso; Gordon Parkinson; Mark Ogden (Indonesian Journal of Chemistry, 2004)
The growth rates of borax crystals from aqueous solutions in the (010) direction at various flow rates were measured. The observed variations of the growth rate can be represented by a normal distribution.  It was found that there is no correlation between growth rate distribution and solution flow under these experimental conditions.